2012
DOI: 10.1590/s0102-09352012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Retardo da realização da IATF sobre o desempenho reprodutivo na estação de acasalamento de vacas de corte lactantes

Abstract: RESUMOCompararam-se efeitos de diferentes protocolos para a IATF com o acasalamento natural (Controle) sobre o desempenho reprodutivo de 249 vacas Aberdeen Angus, distribuídas em cinco grupos: Controle (n=50); Crestar 2º uso (n=64); OvSynch (n=65); Primer 1ºuso (n=35) e Primer 2º uso (n=35). A IATF dos animais dos grupos Crestar 2º uso, OvSynch, e Primer 1º uso foi realizada 27 dias após o início da estação do grupo controle e a IATF do grupo Primer 2º uso ocorreu 38 dias após o início da estação do grupocontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…The results of this study also disagree with those of Gottschall et al (2012), who showed no significant difference in reproductive efficiency of beef heifers under different mating systems (TAI + NS and NS only). This can be explained by the difference in breed (Aberdeen Angus) and especially the hormonal protocol to which the animals were subjected (without the use of eCG).…”
Section: Discussioncontrasting
confidence: 99%
“…The results of this study also disagree with those of Gottschall et al (2012), who showed no significant difference in reproductive efficiency of beef heifers under different mating systems (TAI + NS and NS only). This can be explained by the difference in breed (Aberdeen Angus) and especially the hormonal protocol to which the animals were subjected (without the use of eCG).…”
Section: Discussioncontrasting
confidence: 99%
“…There is no effect of intravaginal progesterone implant of up to third use on the pregnancy rate of heifers 2 and 3), demonstrating that intravaginal progesterone(P4) devices can be reused, allowing the start of the synchronization of the cycle from lower concentrations of this hormone, without reducing conception rates, being a viable and efficient way to perform the TAI Medalha et al, 2015). The results of this work corroborate those published in the literature on the reuse of heifer progesterone device implants up to 3 times (Carvalho et al, 2019;Medalha et al, 2015;Gottschall et al, 2012). The use of fourth-use intravaginal progesterone devices is an effective alternative for inducing puberty in heifers, thus, the authors reported a pregnancy rate of 35.14% in this category (Coelho et al (2021), and in the same In this sense, Figueredo et al, (2019) found a pregnancy rate of 48.18% also in beef heifers and under conditions similar to those observed in this study.…”
Section: Variable Odds Ration P Valuesupporting
confidence: 81%
“…It is also possible that the specialization of beef cattle will occur in other regions, in breeding and fattening systems, due to the soil and climate conditions typical of each region and better access to markets for commercialization. In this context, Gottschall et al [43] demonstrated that the standardization of the cattle herd and carcasses aims to facilitate health management and improve the marketing stage.…”
Section: Discussionmentioning
confidence: 99%